Impact of Government Training and Mentoring on MSME Productivity - Disvara, Savira; Bintoro, Nugroho Suryo (Journal of Development Economic and Social Studies, 2026)
The development of Micro, Small, and Medium Enterprises (MSMEs) is a priority in improving the local economy, especially in Malang City. This study aims to analyze the influence of training and mentoring provided by the Malang City Government on increasing the productivity of MSMEs. Using a quantitative descriptive approach and explanatory research, data was obtained through a questionnaire distributed to 100 MSME enterpreneurs and analyzed using multiple linear regression. The results show that training, which includes financial management and marketing strategies, as well as mentoring, such as intensive mentoring and access to resources, has a significant positive influence, both partially and simultaneously, on increasing the productivity of MSMEs. This research emphasizes the importance of the government's active role in providing sustainable training and mentoring, in order to increase the competitiveness of MSMEs and their contribution to the economic welfare of the community. The implication of this study is the need to increase the intensity and scope of training and mentoring programs by the government to support the sustainable growth of MSMEs.